2017
DOI: 10.3844/ajassp.2017.583.591
|View full text |Cite
|
Sign up to set email alerts
|

Rutting and Fatigue Cracking Susceptibility of Polystyrene Modified Asphalt

Abstract: Abstract:The absence of studies investigating the influence of waste Polystyrene (PS) on the performance characteristics of rutting resistance and fatigue cracking resistance of the indigenous asphaltic materials Trinidad Lake Asphalt (TLA) and Trinidad Petroleum Bitumen (TPB), has hindered the possible use of PS as a performance enhancer as observed with other asphalts from different sources thus also developing a sustainable approach for the disposal of PS. The influence of PS on TLA and TPB was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…PS foam represents 70% of the total plastic waste in the oceans due to its low recycling rate. Approximately 3 million tons of PS waste are threatening the environment due to their chemical stability [5][6][7][8]. Although this threat is tried to be eliminated through landfills and incineration, landfill brings an extra cost, and incineration results in toxic gas emissions, which is detrimental to the environment [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PS foam represents 70% of the total plastic waste in the oceans due to its low recycling rate. Approximately 3 million tons of PS waste are threatening the environment due to their chemical stability [5][6][7][8]. Although this threat is tried to be eliminated through landfills and incineration, landfill brings an extra cost, and incineration results in toxic gas emissions, which is detrimental to the environment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric materials are also considered a good bitumen modifier because of their chemical structure composed of mostly carbon elements [7]. Thus, many studies have been done on asphalt modification with polymeric materials such as PP [9], PE [10], and PS [8,[11][12][13][14]. For instance, Vila-Cortavitarte et al (2018) has performed a life cycle assessment on waste PS modified bitumen and they suggest that using modified bitumen might reduce its environmental impact significantly because it provides longer performance life [14].…”
Section: Introductionmentioning
confidence: 99%
“…16 The use of waste polymeric wastes to possibly improve asphalt pavement performance while simultaneously solving the environmental problem associated with disposal has been receiving research attention with encouraging results in Trinidad and Tobago. 3,5,17 -21…”
Section: Introductionmentioning
confidence: 99%
“…3 TLA has been internationally well established as a commercial product and a source of superior quality asphalt (due to its consistent properties, resistance to cracking, stability and durability compared to other asphaltic materials) and is often specified as a mandatory ingredient for paving in high demand situations such as those encountered in airport runways. [4][5][6] Research has shown that the unique fractional, chemical and functional group composition of TLA determines its strength, durability and resistance to ageing and weathering. 2,3 Asphalt's most valuable and widespread usage is for that of paving.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation